Redesigning the Element Profile of Air Preheater in Coal-fired power plants for Emission Reduction and Efficiency Improvement - SUSILO, Sofiyan Dwi; TRISTANTO, Andhika Dwipradipta; PRASETYA, Wahyu; ICHWAN, Munirul; SIHOTANG, Fernando; INTAN, Indo; KARNYOTO, Andrea Stevens (PT Keberlanjutan Strategis Indonesia, 2024)
PT PLN Nusantara Power Unit Pembangkit Tanjung Awar-Awar (UPTA) is a state-owned company that supplies electricity to areas of Java and Bali. Using coal as the main fuel, UPTA currently has two mills that each has capacity of 350 MW in coal-fired mode. Since the last few years, UPTA has been focusing on bringing efficiency into its overall operations, maximizing efforts for an improved output, modernizing machinery, and reducing emissions. After conducting routine inspection and examinations, UPTA decided to improve the air preheating element, so-called air preheater (APH), as an enabling condition to heat both the primary and secondary air to a temperature required for effective combustion in a boiler. To seek for an optimal APH, a redesign project was initiated to primarily change the element profile from a distorted wavy flow path to a linear flow path. The profile surface was coated with an added